Development of a clinical pathway for behavioural and psychological symptoms of dementia care: A tool to improve resident outcomes. (31st May 2022) - Kennedy, Kate J.; Eckert, Marion; Forsythe, Deborah; Wagner, Joanne; Sharplin, Greg
Abstract: Objectives: Clinical pathways are used to improve the quality of care, reduce variation and maximise health or treatment outcomes in selected populations. The aim of this study was to develop a draft clinical pathway based on the best practice evidence for use in the management of behavioural and psychological symptoms of dementia (BPSD) in residential aged care facilities (RACFs). Methods: The pathway was developed using the best practice evidence from clinical practice guidelines, operational guides and a systematic literature review. A multidisciplinary team of health professionals and researchers worked in an iterative process to contextualise the proposed pathway to local needs and context, and improve its clarity and user‐friendliness. The pathway was then re‐assessed for accuracy and adherence to the evidence. Results: The draft pathway outlines processes for BPSD prevention, watchful waiting for mild‐to‐moderate BPSD, and specific interventions for severe BPSD. Ongoing risk assessment is required throughout, and non‐pharmacological options are first‐line interventions. Person‐centred care was found to be an important care component across all three phases. An instruction guide with colour‐coded flow charts was developed to assist staff with determining the best care and treatment for each person living with dementia. Feasibility testing is underway. Conclusions: A draft clinical pathway based on clinical practice guidelines was developed to enhance the translation of evidence into practice for the management of BPSD, by nursing and clinical leaders in RACFs.